Réflexions générales sur la politique de partenariat à l'école - Jean-Jacques Sarfati
The purpose of this article is to think about the partnership policy at school (in France for the juridical approach and al around for the others ways of thinking) by trying a transversal view on this problem. We want to show the extreme diversity of this policy and the great difference between theory and practice. We also want to think a method for perform this sort of partnership and show the two sorts of view on this question: moral or inspired by a Machiavelli philosophy in a French context of suffering.